Region Of Interest Detection In Thermal Images Of Dc Motor And Average Temperature Calculation - Tuan Nur Atikah, Tuan Shukri (2022)
Heat is a common early sign of equipment breakdown or malfunction, thus preventative maintenance programmes must be closely monitored. Calculations are required in motor thermal modeling to produce the convection thermal coefficient. The coefficient is dependent on the average temperature of the motor surface, which can be determined with a thermocouple. Another option is to use a thermal imaging camera. Thermal imaging is useful for detecting a lack of appliances uniformity by detecting hot and cold areas in surface temperature via infrared image capture. Testo Software have limitation tools to define these regions, such as rectangles, squares, circles, and ellipses because the background reading affecting the average temperature of ROI. This paper aims to detect Region of Interest (ROI) and to calculate average temperature that contains a segmentation algorithm by using Thresholding method and lastly to compare the result between Testo Software and Thresholding method.